Practising Sunnah for reward of heaven in the afterlife: The expansion of cadar wearing among urban Muslim women in Indonesia. Issue 145 (2nd September 2021) - Nonaka, Yo
ABSTRACT: This article discusses the recent phenomenon of more women wearing a cadar (niqab) in Indonesia, particularly among relatively young, urban Muslim women. Although there has been quite a few studies about wearing the hijab and Islamic clothes in Indonesia, there remains a dearth of research on the wearing of a cadar . Most previous studies have discussed it as a practice that is distinctive among women in limited groups, such as the Salafis. However, the number of cadar wearers has increased rapidly in recent years, such that it has now become a controversial issue in society. This study is based on the narratives of interviewees in their twenties to forties who wear cadar in Jakarta, Bandung and Makassar, as well as an analysis of the teachings of some preachers and the social media posts of influencers who encourage women to wear it . It describes the expansion of cadar wearing among urban Muslim women and discusses its continuity from the rise of veil wearing in the past.